Towards AI education: qualitative analysis of the perceptions of professors at a regional public university - Marcelo Rioseco País; Rodrigo Vargas Vitoria; Cristian Martínez Salazar; Juan Silva Quiroz (Social Sciences and Humanities Open)
This qualitative-interpretative study analyzed the perceptions of academics from the Faculty of Education of a regional Chilean public university about artificial intelligence (AI) and its potential impact on higher education. Semi-structured interviews were conducted with a purposive sample of five professors, exploring their conceptions, experiences, and opinions about AI. The collected data were transcribed and coded using the Nvivo 12 Plus software, identifying emerging themes and categories. The results revealed four global categories: characteristics of AI, AI in education, AI in the local context, and concerns about AI. Participants recognized the transformative potential of AI in teaching and learning, highlighting its ability to optimize tasks, generate materials, and facilitate processes. However, they expressed concerns about effectively integrating these technologies into educational practice, emphasizing the need for an ethical and responsible use that fosters students’ critical thinking. The study highlights the importance of teacher training and institutional policy development in harnessing the benefits of AI in higher education while addressing the challenges and concerns associated with its implementation.